Análise exploratória dos impactos das decisões de marketing sobre o desempenho de entrega da área de operações a partir de redes neurais artificiais - Souza, Alex Marques de (Universidade do Vale do Rio dos Sinos, 2013)
Companies should be constantly evolving as its performance due to competition on the market. Therefore, it is necessary to know what the market wants and manufacture this necessity with high operation performance, in order to compete on the market. At this time, come into play two functional areas fundamental to making this practice a reality, they are: Marketing and Operations. These two functional areas, due to the characteristics of their roles and responsibilities, may naturally lead to conflict among themselves. Conflicts begin from the moment the area of operations does not meet the deadlines decided and defined by marketing to meet the market demand. These conflicts can not be eliminated but can be kept under control from the knowledge of the effects of late delivery generators. Therefore, it is necessary to know the impact of decisions in the area of marketing delivery performance in the area of operations. Therefore, the objective of this research is to identify marketing decisions and how their impact in the delivery performance on operation area. To meet this goal, Artificial Neural Networks, with their ability to analyze problems of real practical field, present himself as the quantitative method indicated. Through analyzes using Artificial Neural Networks, we found that marketing decisions related to the composition of the channel are the biggest influence on the performance of the delivery area of operations. This conclusion leads to greater understanding of the impacts that marketing decisions have on performance delivery area of operations, since this knowledge can be applied in practical and scientific field in the quest to meet the marketing needs with the best delivery performance ; offering to the market, therefore, that competitive edge.
Keywords: Marketing; Operações; Desempenho; Conflito entre marketing e operações; Entrega; Nível de serviço; Operations; Performance; Conflict between marketing and operations; Delivery; Service level; ACCNPQ::Engenharias::Engenharia de Produção